2000
DOI: 10.1103/physrevlett.84.935
|View full text |Cite
|
Sign up to set email alerts
|

New Structural Model forSi/SiO2Interfaces Derived from Spherosiloxane Clusters: Implications for Si2pPhotoemission Spectroscopy

Abstract: In this Letter, we investigate the Si/SiO(2) interface structure formed by the chemisorption of H8Si8O12 and other spherosiloxane clusters on Si(100). Using transition state calculations, we clearly demonstrate that the clusters do not bond to the Si(100) surface via single vertex attachment as proposed previously, but rather attach via Si-O bond cleavage. This alternative cracked cluster geometry allows us to predict the photoemission features of spherosiloxane clusters on Si(100) without invoking second near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…3 Although satisfying the requirements mentioned, Y 2 O 3 receives less attention than other oxides because of its affinity for water absorption. 5,6,9,12,13 The challenge of investigating the interface between metal oxides with silicon is that the Si 4ϩ binding energy of an Si-Ometal bonding environment often obscures the Si 3ϩ and Si 2ϩ interface states. 4 We have studied the interface between Y 2 O 3 and the silicon substrate with soft x-ray photoelectron spectroscopy ͑SXPS͒ using synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although satisfying the requirements mentioned, Y 2 O 3 receives less attention than other oxides because of its affinity for water absorption. 5,6,9,12,13 The challenge of investigating the interface between metal oxides with silicon is that the Si 4ϩ binding energy of an Si-Ometal bonding environment often obscures the Si 3ϩ and Si 2ϩ interface states. 4 We have studied the interface between Y 2 O 3 and the silicon substrate with soft x-ray photoelectron spectroscopy ͑SXPS͒ using synchrotron radiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, a larger calculated energy barrier compared to that of the cracked cluster mechanism is believed to make the monovertex attachment product inaccessible. Therefore, it was concluded that the cracked cluster configuration would be kinetically preferred [12]. Can one distinguish between these two models via the STM data?…”
mentioning
confidence: 98%
“…How does this analysis assist in the determination of the bonding geometry? Previous studies have produced two leading cluster bonding models: (1) the "single vertex attachment" configuration [5,6] and (2) the "cracked cluster" configuration [12]. The single vertex attachment model involves Si-H bond activation and cluster attachment to an individual silicon dimer atom.…”
mentioning
confidence: 99%
“…[9][10][11][12] The cracked cluster model features Si-O bond scission along a cluster cage edge, resulting in a bridged bonding configuration across a Si dimer. 13,14 For these models, the Si 9 H 12 cluster was employed to simulate the silicon surface dimer to which the cluster is bonded. Densityfunctional theory calculations were performed using the B3LYP functional and the 6 -31G * * basis set and the SCF calculations were allowed to converge to final ground states.…”
Section: Model Of the Sample Surfacementioning
confidence: 99%
“…1(b)]. 13,14 Although structural assignments based upon XPS 9,10 and RAIRS 11 data have been controversial, interpretations of STM data, based largely on a comparison between experimental results and electron density maps derived from nonlocal density-functional theory (DFT) calculations, strongly support the monovertex attachment model. 12 However, the simple model previously utilized for the purposes of this comparison does not address the discrepancy between the measured experimental apparent height of the cluster and its actual geometric size.…”
Section: Introductionmentioning
confidence: 96%